The Risk Game: a critical discourse perspective on the construction and transference of pensions risk - Read Shepley, Linda M. (2017)
Financial retirement risk is one of the biggest dilemmas faced by individuals and societies in late modernity. It is an unintended consequence of over fifty years of social, scientific and economic development. These have produced ageing citizens, who spend too much and save too little. In response, economists argue that more of the State's pension risk must be transferred to the individual. To achieve this, the UK Government introduced auto-enrolment workplace pension policy to 'nudge' spenders into becoming savers. In this thesis, I use this change in legislation to explore what happens when the libertarian paternalism, implicit in behavioural economic theory, enters the real world. Adopting a sociological approach through critical discourse analysis, I explore the different interpretations of financial risk constituted by the State, media, employers and employees. The study traces how the State has attempted to transfer financial risks onto individuals through a process labelled the risk game. This involves constructing and legitimising discourses of winners versus losers, spenders versus savers and experts versus lay people. However, the risk game is not straightforward. Other participants, such as the press, employees and employers, play with the discourses government set in motion and through their discursive reinterpretations, they attempt to transfer the risk onto the other players, including the government. The discursive strategies adopted include: the passive matching effect, used by employees to pass the responsibility to the employer; and the avoidance effect, where employees return the risk to the State in a new form. Other employees actively choose to play by different rules, using the operative visualization of risk, through discourses of long-term vision and self-reflexive action. Understood as the risk game, this thesis reveals flaws in the implementation of the government's auto-enrolment pension policy. Informed by Beck’s theories, the thesis concludes that rather than nudging individuals, the State can only transfer responsibility for risk through coercion or with the recipient’s understanding and active engagement. This has implications for pension policy and the pensions industry and casts doubt on the prevailing economic theory that spenders can be nudged into becoming savers.